The cost of living crisis: A pre-Budget briefing - Jonathan Cribb; Robert Joyce; Heidi Karjalainen; Sam Ray-Chaudhuri; Tom Waters; Thomas Wernham; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2023)
The recent surge in inflation, driven by spectacular increases in energy prices, has driven sharp falls in household living standards, huge government intervention to try to mitigate it, and serious policy headaches. As such it continues to be the backdrop behind many of the most pressing issues that will face Chancellor Hunt when he delivers his first Budget on 15 March. This short report analyses the latest outlook for inflation, how this varies across households and is impacted by the government's interventions on consumer energy prices, and the resulting effects on real earnings and benefit levels.
Keywords: 330; Consumption and prices; Poverty; inequality and social mobility; Spring Budget 2023; Inflation; Inequality; Pay